Implementasi dan Optimalisasi Digitalisasi Pembukuan Ekspedisi pada Corporate Finance PT PLN Nusantara Power Services: (Kantor Pusat PLN – NPS Sidoarjo) - Kevin Ramadhany Sukmana (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The budget division has responsibility for tasks that are usually carried out including financial management, analysis and budget control in the company The aim of this research is to determine the implementation and optimization of digitalization of expedition bookkeeping in the budget division by employees of the State Electricity Company Nusantara Power Services (PT. PLN-NPS) at the Sidoarjo head office, East Java. This research uses field research methods by collecting data through reviewing internship activities and using previous research regarding the budget division. The research results show that the implementation and optimization of digitalization of expedition bookkeeping in the budget division can helps all employee needs and already has an effective system in its use.